Exposure to specific polyfluoroalkyl chemicals is associated with cardiovascular disease in US adults: a population-based study - Xiao, Wenwen; Jian, Guojin; Ma, Fei; Li, Hong; Yang, Xiaohong; Zhang, Hengyang; Cao, Yongping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPolyfluoroalkyl chemicals (PFCs) present potential health risks due to their persistence and bioaccumulation. However, there is currently insufficient evidence regarding their impact on cardiovascular disease (CVD). Consequently, it is imperative to investigate the correlation between PFCs and CVD.MethodsThe data was collected from National Health and Nutrition Examination Survey in 2005–2012. Logistic regression models were employed to assess the association between single PFC and CVD. Generalized additive model (GAM) was used for evaluating nonlinear relationships. Subgroup analyses were conducted to explore interaction effects. Bayesian kernel machine regression (BKMR) and weighted quantile sum (WQS) models were used to evaluate the joint effect of PFC exposures on CVD.ResultsIn logistic regression, PFDE, MPAH, and PFUA were positively associated with CVD. In the GAM, there was a significant nonlinear relationship between MPAH and CVD. Subgroup analysis revealed the interaction of gender and race in the effects of PFCs and CVD. PFUA was positively correlated with CVD in males but show no significant difference in females. PFDE was positively associated with CVD among non-Hispanic white individual. The results of BKMR indicated that the impact of mixed PFCs on CVD increased initially and then weakened, showing an overall positive trend. The results of WQS suggested that PFDO contributed most to the effect.ConclusionOur study showed that serum PFDE, MPAH, and PFUA levels were positively correlated with CVD. PUFA was found to interact with gender and race in relation to CVD. A general positive correlation exists between mixed exposure to PFCs and CVD, with PFDO being the most contributory PFC. Our study provided important evidence for probing the impact of PFCs on CVD and laid a foundation for further mechanism research.